Late Miocene Potamarchine Rodents from Southwestern Amazonia, Brazil - With Description of New Taxa - Kerber, Leonardo (2016)
The fossil rodents from the southwestern Amazonia of Brazil have been studied since the first half of the 20th century. Several caviomorph rodents were reported for the Neogene of this region, mainly neoepiblemids and dinomyids. Until recently, the record of dinomyids in the Solimões Formation (Late Miocene) was predominantly based on a few isolated teeth, which made it difficult to make more accurate taxonomic identifications due to the scarcity of diagnostic characters. Here, new remains, more complete than those previously reported, of potamarchine dinomyids from the Neogene of Brazil are described. A new species of Potamarchus and a new genus and species of a Potamarchinae are erected. In addition, new material of Potamarchus murinus and Potamarchus sp. is identified. These data suggest a higher diversity of dinomyids in in the western Amazonia than previously supposed.